A factor and operational approach to command and control of service and combat activities of military units - Belay, S. V.; Osypenko, S. М. (Honor and Law, 2019)
The essence of a factor and operational approach to the command and control sphere is considered. A scheme of a unit combat and service activity command and control based on the factor and operational approach is developed. A mathematic model is proposed and a sample of a problem solution to determine a list of events to ensure optimal values of a general indicatorof service and combat activities of the Interior Troops units and and the resources required for their realization is given.